The Miss Rate for Colorectal Adenoma Determined by Quality-Adjusted, Back-to-Back Colonoscopies - Ahn, Sang Bong; Han, Dong Soo; Bae, Joong Ho; Byun, Tae Jun; Kim, Jong Pyo; Eun, Chang Soo (Gut and liver, 2012)
Colonoscopy is considered to be the gold standard for detecting adenomatous polyps. Polyps are missed during colonoscopic examination at a rate that varies from 6% to 27%. The adenoma miss rate affects colonoscopic surveillance intervals and procedural quality. We aimed to assess the adenoma miss rate and the variables affecting the rate using same-day, quality-adjusted, back-to-back colonoscopies. This prospective study was performed at a single institution and included 149 patients. Two consecutive same-day colonoscopies were performed by two experienced endoscopists. The adenoma miss rates and variables affecting the missed adenomas, including polyp characteristics and procedure times, were evaluated. The miss rates of polyps, adenomas, and advanced adenomas were 16.8%, 17%, and 5.4%, respectively. The smaller polyps and increased number of polyps detected during the first colonoscopy were more likely to be missed. A longer insertion time during the colonoscopy was correlated with an increased adenoma detection rate. There was a significant miss rate in the detection of colonic adenomas even in quality-adjusted, back-to-back colonoscopies. The adenoma miss rate can be reduced with a sufficient observation time during colonoscopic insertion. The development of specific technological methods to reduce the adenoma miss rate is necessary.